Pengaruh Workshop dan Perencanaan Pengajaran Terhadap Kinerja Guru - Kuswahyuningsih Kuswahyuningsih (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
Absrak: This study aims to determine the influence of the importance of workshops and teaching planning on teacher performance both partially and simultaneously. The research approach uses a quantitative approach, with 50 sample respondents from 50 Sukoharjo MAN teachers as a population. They are processing data using multiple linear regression analysis. The results of the study show that there is a positive influence on workshops and teaching planning both partially and simultaneously, which is evidenced by the results of t counts of 6.572X1 and 3.794X2, which are positive. There is a significant influence on teacher performance, as evidenced by the results of a determination coefficient of 0.929, so there is an influence of another variable of 0.071. In conclusion, the higher and better the workshops and teaching planning are given, the higher the teacher's performance shown to the madrasah. Keywords: Teacher Performance, Teaching Planning, Workshop